ANALISIS KUALITAS LAYANAN WEBSITE DAN PROMOSI E-COMMERCE TERHADAP KEPUTUSAN PEMBELIAN PRODUK PADA SHOPEE - Dendy Kurniawan; Edy Siswanto (Journal of Global Business and Management Review, 2022)
This quantitative research was carried out with the object of research being shopee e-commerce users who were chosen randomly and at least had made a purchase of products or services once. While the number of population samples in this study were 100 people, the majority of whom were students. While the data collection technique using a google form questionnaire. The results obtained from data processing, show the multiple linear regression equation Y = 5.860+ 0.142X1 + 0.335X+e. There is a positive and significant effect of service quality on shopee product purchasing decisions, as evidenced by the value of a significant level of service quality of 0.002. There is also a positive and significant effect of promotion on product purchasing decisions at shopee, which is proven by the significant value below 0.002. F test obtained a significant level of 0.000. These results indicate that there is a joint influence between service quality and promotion on product purchasing decisions at shoppe because the value is below 0.05. while the value of determination is 0.578 or 57.8%. This can be interpreted that the quality of services and promotions affect product purchasing decisions on e-commerce shopee by 57.8, while the remaining 42.2% is influenced by other factors that are not included in the scrutiny.